Ultrasonography in congenital clubfoot: what measurement predicts outcome of Ponseti treatment ? - Abdul Razak, Ardilla Hanim; Kim, Jong Seop; Cho, Tae-Joon; Shin, Chang Ho; Cheon, Jung-Eun; Choi, In Ho; Yoo, Won Joon (2019)
Purpose: To find objective ultrasonographic indices those are associated with severity of deformity and outcome of Ponseti method in congenital clubfoot Methods: We retrospectively reviewed the ultrasonographic findings observed at the time of initiation of treatment with Ponseti method in 44 congenital clubfeet (32 patients, unilateral:bilateral=20:12, right:left=23:21). There were 27 boys and 5 girls, and the mean age at the time of ultrasonographic evaluation was 51.2 days (range 5 -152). Manipulation and serial plaster cast was applied 5.4 times per foot on average (range, 4-9) and percutaneous tenotomy of the Achilles tendon was performed in 40 feet. Ultrasonographic measurements included medial malleolus-navicular distance (MND), MND under stress maneuver (abduction and dorsiflexion), change in MND by abduction, talar length, talar depth (distance from the skin to the talus at the level of medial malleolar tip), talar angle, presence of fibrotic band or echogenic soft tissue in the medial malleolar-navicular region, calcaneocuboid subluxation, and lateral malleolus-calcaneus distance. All distance measurements were adjusted by talar length to compensate for foot size variance. These indices were analyzed to determine what measurement was correlated with initial Dimeglio score (Spearman correlation coefficient) and what measurement can be used to predict outcome of Ponseti method (Mann-Whitney test). Results: The mean Dimeglio score was 10.7 (range, 5-20) at the time of initiation of treatment and 5.2 (range, 4-10) at the mean 6.0 year-follow up evaluation (range 1.7 – 10.2). The talar depth was correlated with initial Dimeglio score (Spearman correlation coefficient 0.563, p=0.00182). Outcome of Ponseti method was defined to be poor when extensive soft tissue release was necessary within 1 year (3 feet) or when soft tissue release and realignment of tarsal bones were followed to correct residual deformity (9 feet), whereas Ponseti method was thought to be excellent when corrected foot was well maintained without any surgery (14 feet) or only tibialis anterior transfer was necessary to correct supination tendency (16 feet). Poor clinical outcome of Ponseti method was negatively associated with the change in MND by abduction (p=0.013) and positively with initial Dimeglio score (p=0.027). Conclusions: Ultrasonography is useful in terms of objective assessment of severity of deformity (talar depth) and has a prognostic value that may predict outcome of Ponseti method (change in MND by stress maneuver) in congenital clubfoot.